Ab Initio Modelling of g-ZnO Deposition on the Si (111) Surface - Alzhanova, Aliya; Mastrikov, Yuri; Yerezhep, Darkhan (MDPI, 2024)
Recent studies show that zinc oxide (ZnO) nanostructures have promising potential as an absorbing material. In order to improve the optoelectronic properties of the initial system, this paper considers the process of adsorbing multilayer graphene-like ZnO onto a Si (111) surface. The density of electron states for two- and three-layer graphene-like zinc oxide on the Si (111) surface was obtained using the Vienna ab-initio simulation package by the DFT method. A computer model of graphene-like Zinc oxide on a Si (111)-surface was created using the DFT+U approach. One-, two- and three-plane-thick graphene-zinc oxide were deposited on the substrate. An isolated cluster of Zn3O3 was also considered. The compatibility of g-ZnO with the S (100) substrate was tested, and the energetics of deposition were calculated. This study demonstrates that, regardless of the possible configuration of the adsorbing layers, the Si/ZnO structure remains stable at the interface. Calculations indicate that, in combination with lower formation energies, wurtzite-type structures turn out to be more stable and, compared to sphalerite-type structures, wurtzite-type structures form longer interlayers and shorter interplanar distances. It has been shown that during the deposition of the third layer, the growth of a wurtzite-type structure becomes exothermic. Thus, these findings suggest a predictable relationship between the application method and the number of layers, implying that the synthesis process can be modified. Consequently, we believe that such interfaces can be obtained through experimental synthesis. © 2024 by the authors. --//-- This is an open-access article Alzhanova, A.; Mastrikov, Y.; Yerezhep, D. Ab Initio Modelling of g-ZnO Deposition on the Si (111) Surface. J. Compos. Sci. 2024, 8, 281. https://doi.org/10.3390/jcs8070281 published under the CC BY 4.0 licence.
This research has been funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan\u2014\u00ABZhas Galym\u00BB 2022/2024 grant No. AP14972733. The European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Ab initio; adsorbed; computational modelling; DFT; material properties; nanoclusters; Si; VASP; ZnO